3D Networks of Carbon‐Coated Magnesium‐Doped Olivine Nanofiber as Binder‐Free Cathodes for High‐Performance Li‐Ion Battery. Issue 17 (29th June 2016) - Ma, Dingtao; Zhang, Peixin; Li, Yongliang; Abdelkader, Amor M.; Singh, Deepak P.; Ren, Xiangzhong; Deng, Libo
Abstract : 3D nanoarchitecture of LiFe0.98 Mg0.02 PO4 /C nanofibers is synthesized by a one‐pot electrospinning method and employed as a binder‐free cathode material for Li‐ion batteries. The novel cathode shows significant improvement in the electrochemical performance, particularly for stability and rate capability due to the unique combination of the interconnected fibrous structure and the high electronic and ionic conductivity induced by Mg‐doping. The LiFe0.98 Mg0.02 PO4 /C nanofiber cathode displays a discharge capacity of 152 mAh g −1 with capacity retention of 98.2% at 0.5 C after 100 cycles. Investigations on the stability and rate capability of the novel porous electrode studied at different rates of 0.05 C to 10 C for 100 cycles also show high capacity values that indicate their potential as cathode materials. Abstract : 3D LiFe0.98 Mg0.02 PO4 /C (LFMP/C) nanofibers are synthesized in one‐step electrospinning process. This method is effective for restricting the aggregation of LFMP nanofibers and uniform coating of a conducting carbon layer on active material surface. This unique interconnected structure enhances the electrode reaction kinetics and reduces the polarization and the Mg doping efficiently enhances the electronic conduction and electrochemical activity.